KOMPARASI POTENSI PIROLISA LIMBAH PLASTIK PERKOTAAN UNTUK MENDAPATKAN BAHAN BAKAR CAIR SETARA BENSIN - Reno Pratiwi; Wiwik Dahani; Kartika Fajarwati H (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2017)
This reseacrh aims to find out how big the potential of processing various types of plastic into fuel equivalent of gasoline. The types of plastics observed are the types that are widely available in urban wastes, the types of Light Density Polyethylene (LDPE), High Density Polyethylene (HDPE) and Polypropylene (PP). Plastic processing using pyrolysis method, with the amount of time and temperature of the process as a variable that observed its effect on the product produced. The analysis of the products using FTIR will be compared with the standard FTIR of gasoline, as well as the density test which is also compared with the standard density of gasoline applicable in Indonesia. The results show that optimum conditions can be achieved at 60 minutes process time, and different process temperatures on each type of plastic. Plastics of LDPE, HDPE and PP types have optimum temperatures of 500 oC, 530 oC and 550 oC, respectively. Percentage of results at optimum time and temperature conditions were 87.3%, 93% and 83%, respectively. Although the percentage of the results obtained is not much different from the other two types of plastics, but based on the similarity of the product with the characteristics of fuel gasoline, PP plastic type gives the closest results in terms of FTIR analysis and measurement of gasoline density. Thus PP type plastic has the potential to develop its processing into alternative fuel equivalent gasoline.